PENERAPAN STANDAR PENGGUNAAN PEMANIS BUATAN PADA PRODUK PANGAN - Indrie Ambarsari; Qanytah Qanytah; Sarjana Sarjana (Badan Standardisasi Nasional, 2009)
The using of artificial sweeteners in food products is more extending, thus evaluation on how food producersimplemented regulation of artificial sweeteners type, maximum level for use, and admonition on product label isneeded. Information was collected according to explanation that written on product packaging (label) such as:type and artificial sweeteners content, and admonition about using and its side effect that based on regulationstated in SNI 01-993-2004 and Indonesian Government Statement No. 69 Year 1999. The food products thatused as sample was categorized in beverages, confectioneries, chewing gum, and dietary supplement products.The observation result showed that many of food products did not add the sweeteners dosage, admonition aboutthe using and it side effect on the label product. Beside that, there were tendency in using more than onesweetener in one product. As for that, the standard or special regulation that regulates the use of artificialsweeteners combination is necessary.